2020
DOI: 10.1111/ina.12648
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of chemical emission rates from cigarette butts into air

Abstract: This study examined airborne emissions from cigarette butts for styrene, 2‐methyl‐2‐cyclopenten‐1‐one, naphthalene, triacetin, and nicotine. Ten experiments were conducted by placing butts in a stainless steel chamber and measuring the chemical concentrations in chamber air. Emission rates were determined from the concentrations. Triacetin and nicotine concentrations were roughly 50% of initial concentrations after 100 hours, while concentrations of other chemicals decayed to less than 10% of initial concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…We currently know very little about how the toxicity of cigarette butts may change over time when in the environment, but recent research indicates that butts continue to exude toxic chemicals into the air at least 1 week after being extinguished (Gong et al 2020). Furthermore, Bonanomi et al (2020) found that cellulose acetate cigarette butts remained toxic to the microalga Raphidocelis subcapitata after 5 years of degradation in the terrestrial environment.…”
Section: Discussionmentioning
confidence: 99%
“…We currently know very little about how the toxicity of cigarette butts may change over time when in the environment, but recent research indicates that butts continue to exude toxic chemicals into the air at least 1 week after being extinguished (Gong et al 2020). Furthermore, Bonanomi et al (2020) found that cellulose acetate cigarette butts remained toxic to the microalga Raphidocelis subcapitata after 5 years of degradation in the terrestrial environment.…”
Section: Discussionmentioning
confidence: 99%
“…While detailed speciation has been carried out for direct emissions from cigarettes, 29,32,[48][49][50] measurements of THS have been relatively limited to a subset of prominent individual compounds. 4,11,12,18,19 Here, we applied a powerful combination of online and offline high-resolution mass spectrometers with so ionization to chemically speciate complex THS mixtures, along with the gases and PM that comprise SHS, from which THS is derived.…”
Section: Speciating the Extensive Chemical Complexity Of Thsmentioning
confidence: 99%
“…The high molecular weight prototypic PAH benzo[a]pyrene, a five-ring PAH, is classified as a Group 1 carcinogen to humans. PAHs are nonpolar and hydrophobic, and many PAHs, especially those of lower molecular weight, are reasonably water soluble, volatile and biodegradable by soil and aquatic microorganisms [40,41]. PAHs tend to accumulate on particles in environments, such as smoke, dust, soil and sediment that facilitate PAH transport in the atmosphere [42] and in soils and groundwater [43].…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…An emerging concern related to CB pollution is the release of nanoparticles found in cigarette smoke, and how these particles can facilitate the transport of surface-bound metals and organic contaminants in the environment [98]. CBs can be sources of several pollutants to the atmosphere, including alcohols, carbonyls, hydrocarbons, and pyrazines [18,40,41]. Given they are a source of toxic chemicals and plastic pollution to the environment, CBs could be categorized as hazardous waste [82,99,100].…”
Section: Cigarette Buttsmentioning
confidence: 99%